Hunter hunter [videorecording (DVD)] - Linden, Shawn; Sullivan, Camille; Sawa, Devon, 1978-; Howell, Summer; Stahl, Nick, 1979- (Shout! Factory, 2021)
A fur trapper leaves his wife and daughter behind to kill a rogue wolf in the isolated wilderness. But they soon become progressively worried when a severely injured man shows up to disrupt their peaceful existence.